Target setting in intensive insulin management is associated with metabolic control: the Hvidoere childhood diabetes study group centre differences study 2005 - Swift, P G F; Skinner, T C; de Beaufort, C E; Cameron, F J; Aman, J; Aanstoot, H-J; Castaño, L; Chiarelli, F; Daneman, D; Danne, T; Dorchy, H; Hoey, H; et al. (Wiley Online Library, 2010)
Objective: To evaluate glycaemic targets set by diabetes teams, their perception by adolescents and parents, and their influence on metabolic control. Methods: Clinical data and questionnaires were completed by adolescents, parents/carers and diabetes teams in 21 international centres. HbA1c was measured centrally. Results: A total of 2062 adolescents completed questionnaires (age 14.4 ± 2.3 yr; diabetes duration 6.1 ± 3.5 yr). Mean HbA 1c = 8.2 ± 1.4% with significant differences between centres (F = 12.3; p < 0.001) range from 7.4 to 9.1%. There was a significant correlation between parent (r = 0.20) and adolescent (r = 0.21) reports of their perceived ideal HbA1c and their actual HbA1c result (p < 0.001), and a stronger association between parents' (r = 0.39) and adolescents' (r = 0.4) reports of the HbA1c they would be happy with and their actual HbA1c result. There were significant differences between centres on parent and adolescent reports of ideal and happy with HbA1c (8.1 < F > 17.4;p < 0.001). A lower target HbA1c and greater consistency between members of teams within centres were associated with lower centre HbA1c (F = 16.0; df = 15; p < 0.001). Conclusions: Clear and consistent setting of glycaemic targets by diabetes teams is strongly associated with HbA1c outcome in adolescents. Target setting appears to play a significant role in explaining the differences in metabolic outcomes between centres.